'Not just one node among many' – plural policing in a state-dominated context: the case of Austria. (2nd January 2017) - Terpstra, Jan
Abstract : One of the most influential approaches in the study of plural policing is the concept of nodal governance of security. This approach is presented as an alternative to the dominant, state-centred model of policing. This paper tries to understand the pluralisation of policing in a continental European context that focuses strongly on the state as the central actor in policing. It deals with one such country, Austria. After a description of the history, constitutional system and culture of Austria, this paper deals with the several public and private aspects of policing in this country. Two elements are quite characteristic of the general attitude concerning plural policing in Austria. There is a widespread reluctance to accept the pluralisation and privatisation of policing. In Austria, plural policing is often a highly politicised issue. Both elements may be understood as resulting from the fact that plural policing is often perceived as a highly sensitive public issue. Seen from the perspective of the continental European countries, there are important reasons for not too readily accepting nodal strategies. In the continental European context, the state is not only more than just 'one node among many'. The theoretical problem is that the nodal perspective does not provide the tools to understand why these countries hold to their stronger orientation towards the state in the matter of policing.